Five Principles of Post-Interpretive Criticism: A Study Guide - Vale, Dorian (MUSEUM OF ONE, 2025)
This concise study guide introduces the foundational framework of Post-Interpretive Criticism (PIC)—a new aesthetic philosophy that centers presence, moral proximity, and restraint in the practice of art criticism. Developed by Dorian Vale, the guide breaks down PIC into five core principles: Restraint over Interpretation Witness over Commentary Moral Proximity over Objectivity Viewer as Evidence Rejection of Performance Each principle is accompanied by a brief case study, reflection exercise, and ethical commentary, making this guide suitable for students, educators, curators, and critics seeking to apply PIC in the field. Instead of decoding the artwork, this framework encourages a posture of reverent presence, allowing the artwork to retain its autonomy and moral gravity. This resource is designed to be taught, discussed, and practiced. It supports classrooms, curatorial programs, writing workshops, and museum education—inviting a new generation of viewers to approach art with humility, silence, and philosophical depth. Vale, Dorian. Five Principles of Post-Interpretive Criticism: A Study Guide. Museum of One, 2025. DOI: 10.5281/zenodo.17077734 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Post-Interpretive Criticism, study guide, art education, critical theory, Dorian Vale, aesthetic philosophy, viewer as evidence, slow looking, ethical criticism, trauma in art, art pedagogy, witness-based art criticism, art classroom resource, art and ethics, moral proximity, presence over interpretation, contemporary criticism, museum education, poetic criticism, art curriculum
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 https://africarxiv.ubuntunet.net/handle/1/10466 https://africarxiv.ubuntunet.net/handle/1/10467 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: Independent Philosopher of Art; The Viewer as Evidence; Alternative art criticism; Interpretive Restraint; Post-Interpretive Criticism; Language as Custody; Radical art restraint; Witness Aesthetics; Restraint in front of art; Museum of One; Art Criticism Ethics; Witness over interpretation; Quiet philosophy of art; The Custodian's Oath; Custodianship of Art; Ethics in Art Criticism; Ethical art theory; Post-Interpretive Lexicon; Art Theory; Erasure as Afterlife; Moral proximity; Stillmark Theory; The Doctrine of Post-Interpretive Criticism; Criticism beyond interpretation; Art as Truth; Post-Aesthetic Critic; Custodian of Witness Aesthetics; Art as Presence; Art Writer and Theorist; Dorian Vale; Aesthetic Philosopher; New art criticism movement; Contemporary Aesthetics